Pemberdayaan Remaja Desa Tegalsari Melalui Kegiatan Ngabuburit Seru Bareng Kakak Muttaqien: Pelatihan Fotografi Bagi Anak Remaja - Acon Hambali (Muttaqien Publishing Pusat Penelitian dan Pengabdian kepada Masyarakat STAI DR. KH.EZ. Muttaqien Purwakarta, 2022)
The month of Ramadan is the most awaited month by Muslims around the world. In Indonesia, there are many moments in the month of Ramadan that are usually filled with one of them ngabuburit, the term ngabuburit comes from an absorption of the Sundanese word, burit in Sundanese is afternoon while ngabuburit means spending time going to or in the afternoon. To make something different today, we need to upgrade it with something meaningful and useful. The Fun Ngabuburit Study with Brother Muttaqien is a program for teenagers who want to learn photography and journalism, packaged like a prayer room or boarding school. This program takes place not before the evening call to prayer but in the morning at school.